2016
DOI: 10.1007/s00540-016-2257-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in obstetric anesthesia and intensive care

Abstract: Magnesium, one of the essential elements in the human body, has numerous favorable effects that offer a variety of possibilities for its use in obstetric anesthesia and intensive care. Administered as a single intravenous bolus dose or a bolus followed by continuous infusion during surgery, magnesium attenuates stress response to endotracheal intubation, and reduces intraoperative anesthetic and postoperative analgesic requirements, while at the same time preserving favorable hemodynamics. Applied as part of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 93 publications
0
19
0
Order By: Relevance
“…All the clinical effects for the use of magnesium sulfate in anesthesia presented by the anesthesiologists participating in this survey have been reported in other publications, including various systematic reviews and meta-analyses, although some of them are still subjects of controversy Beşogul et al, 2009; Gozdemir et al, 2010; Rhee et al, 2012; Abdulatif et al, 2013; Rotava et al, 2013; Agrawal et al, 2014; Ahsan et al, 2014; Crowther et al, 2014; Kahraman and Eroglu, 2014; Kew et al, 2014; Marzban et al, 2014; Rodrigo et al, 2014; Srebro et al, 2014; Uludag et al, 2014; Berhan and Berhan, 2015; Kim et al, 2015; Safavi et al, 2015; Vigil-De Gracia and Ludmir, 2015; Demiroglu et al, 2016; Green, 2016; Griffiths and Kew, 2016; Jangra et al, 2016; Juibari et al, 2016; Maged et al, 2016; Naghipour et al, 2016; Rodríguez-Rubio et al, 2016, 2017; Soltani et al, 2016; Thomas and Behr, 2016; Ulm et al, 2016; Vendrell et al, 2016; Xie et al, 2016, 2017; Brookfield et al, 2017; Haryalchi et al, 2017; Kutlesic et al, 2017; Lecuyer et al, 2017; McKeown et al, 2017; Mendonca et al, 2017; Salaminia et al, 2018; Zhang et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the clinical effects for the use of magnesium sulfate in anesthesia presented by the anesthesiologists participating in this survey have been reported in other publications, including various systematic reviews and meta-analyses, although some of them are still subjects of controversy Beşogul et al, 2009; Gozdemir et al, 2010; Rhee et al, 2012; Abdulatif et al, 2013; Rotava et al, 2013; Agrawal et al, 2014; Ahsan et al, 2014; Crowther et al, 2014; Kahraman and Eroglu, 2014; Kew et al, 2014; Marzban et al, 2014; Rodrigo et al, 2014; Srebro et al, 2014; Uludag et al, 2014; Berhan and Berhan, 2015; Kim et al, 2015; Safavi et al, 2015; Vigil-De Gracia and Ludmir, 2015; Demiroglu et al, 2016; Green, 2016; Griffiths and Kew, 2016; Jangra et al, 2016; Juibari et al, 2016; Maged et al, 2016; Naghipour et al, 2016; Rodríguez-Rubio et al, 2016, 2017; Soltani et al, 2016; Thomas and Behr, 2016; Ulm et al, 2016; Vendrell et al, 2016; Xie et al, 2016, 2017; Brookfield et al, 2017; Haryalchi et al, 2017; Kutlesic et al, 2017; Lecuyer et al, 2017; McKeown et al, 2017; Mendonca et al, 2017; Salaminia et al, 2018; Zhang et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our survey demonstrated similar results. Despite the occurrence of reports of serious AEs, the use of magnesium sulfate can be safe in recommended doses with close monitoring of patients (Kutlesic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This effect should be most profound on the ion with the highest charge density, magnesium at 30.72 e/nm 2 . As all ions in bulk water will have the same charge density, the important biological ions calcium and magnesium must be dehydrated to be distinguished at the molecular level [6][7][8][9][10][11][12][13]. Calculations will determine the dehydration needed to distinguish calcium from magnesium, which has a higher charge density than calcium [5] and therefore binds water more tightly [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…The element is known to attenuate stress responses to endotracheal intubation, preserve favorable hemodynamics, block acetylcholine releases at neuromuscular junctions, and potentiate the effects of nondepolarizing neuromuscular blockers. 1 Moreover, studies found that magnesium sulfate reduces anesthetic requirements, shortens anesthetic induction with propofol and diminishes total postoperative analgesic consumption with no adverse maternal or neonatal effects. 2 , 3 Additionally, the element has potential analgesic and sedative properties; therefore, it is useful as an adjuvant during general anesthesia.…”
mentioning
confidence: 99%